Prodromus of a fern flora for Bolivia. XLI. Errata - Kessler, Michael; Smith, Alan R.; Schwartsburd, Pedro B.; Moran, Robbin C.; Matos, Fernando B. (Phytotaxa, 2019)
We correct a number of omissions and errors in the previous series of publications of the “Prodromus of a fern flora for Bolivia”. Most importantly, we correct the combining authorship for Didymoglossum punctatum subsp. sphenoides (Kunze) Boudrie & Cremers, add missing information on Elaphoglossum latevagans Mickel, and validly publish the new combination and status for Hypolepis rigescens var. buchtienii (Rosenst.) Schwartsb. and new combination Christella abrupta (A.R.Sm.) A.R.Sm., previously called C. grandis, which was invalidly published.